BRAF, KIT, NRAS, GNAQ and GNA11 mutation analysis in cutaneous melanomas in Turkish population - Ismail Yilmaz (Indian Journal of Pathology and Microbiology, 2015)
Background: KIT and mitogen-activated protein kinase cascade are important for melanomagenesis. In the present study, we analyzed the frequency of BRAF, NRAS, KIT, GNAQ and GNA11 gene mutations and investigated their association with clinicopathological features of melanomas in Turkish population. Materials and Methods: Forty-seven primary cutaneous melanomas were included in our study. Sanger sequencing method was used for mutation analysis in all cases. Results: Mean age was 62.1 (29-101) years. Female:male ratio was 17:30. Among 47 melanomas, 14 (29.8%) BRAF, 10 (21.3%) NRAS, 4 (8.5%) KIT and 1(2.1%) GNAQ gene mutations were detected. Two of the KIT mutations were found in acral lentiginous melanoma (ALM). In the head and neck region, mutation frequency was significantly lower than in other locations (P = 0.035). The only GNAQ gene mutation (p.Q209L) was detected in a melanoma arising from blue nevus located on the scalp. None of the melanomas harbored NRAS exon 2, KIT exon 13/17/18, GNAQ exon 4 and GNA11 exon 4/5 mutations. Overall mutation frequency did not show significant difference between metastatic (8/14, 57.1%) and nonmetastatic (18/33, 54.5%) patients. We did not observe any significant association between mutation status and gender or age of various patients. Conclusions: Our results support that BRAF and NRAS gene mutations are common in cutaneous melanomas. The activating mutations of KIT gene are rare and especially seen in ALM. GNAQ and GNA11 mutations are infrequent in cutaneous melanomas and may be associated only with melanomas arising from blue nevus.